(untitled) (Nepal Medical College Journal, 2020)
Gastric cancer is the fourth most frequently occurring malignancy, after lung, breast and colorectal cancer, and the second most common cause of death from cancer worldwide. The global incidence of gastric cancer shows wide geographic variation with a 15-20 fold difference between high and low incidence region. Therefore the prevention of gastric cancer represents one of the most important aspects of any cancer control strategy around the world. From the hospital based data in Nepal gastric cancer is the third most common cancer in males and the sixth common cancer in females. An observational hospital based descriptive study was carried out in the Oncology Unit of (NMCTH) from 2013-2018 on relationship between salty processed food consumption and increased possibility of development of gastric cancer in different ethnic groups of Nepal. Fifty-four diagnosed gastric cancer patients were enrolled and their dietary habits were extensively looked into. Of these 55.6% (30) were males and 44.4% (24) were females. The patient’s age ranged between 25-75 years and the peak incidence was in age group 41-60 years. The habit of consumption of smoked meat was higher (77.8%) than the consumption of packed food and fermented food. Tibeto-mongoloid ethnicity was found to have more prevalence (64.8%) to gastric cancer. The common site of presentation of gastric cancer was at the antrum (44.4%) and tubular adenocarcinoma was the most common type. It was the Tibeto-mongoloids whose food habit pattern comprised of major consumption of salty processed food and having more preference for salty processed food in daily life had increased high risk of gastric cancer than the other ethnic groups. This concludes that food consumption pattern play a critical role in the incidence of gastric cancer and dietary modification to reduce salt and salted food is a practical strategy with which gastric cancer risk can be prevented in these high risk ethnic group of Nepal.